Memórias e histórias de trabalhadores em luta pela terra: Fernandópolis-SP, 1946-1964 - Moreira, Vagner José (2009)
The research aims to quest the historical and social process of memories construction about the workers' social movement in June 1949 in Fernandópolis-SP, commonly known as "communist insurgence or movement of agrarian revolution . Workers mobilized and organized themselves into various social movements that struggled against exploitation and domination lived in the field and city in the socialy shared environment of late 1940 and the following two decades. The historical process experienced by the workers was related to extreme situations involving pressure and exploitation of the large landowners, the organization of various movements, the politic struggle, the political and police repression of the DOPS and life in hiding; finally, limits, pressures and expectations of the daily life. Among the various struggles that the organized, the struggle for land marked a politicization moment of the class struggle where workers have established ways of life and struggle by themselves. The questioning were outlined in the convergence of daily life and the meanings that workers assigned to the process of developing several projects for their lives, among them, the struggle for land, in relation to meanings and hegemonic values and practices. We inspect in the criminal research, police investigations, records of DOPS, the press and oral narrative. Therefore, the historical and social process of construction of memories about the social movement of workers in June 1949, the experiences of the struggle for land and political militancy in Fernandópolis led me to identify the memory as one of the places of contention for hegemony in the city and workers movement at June 1949 as the expression of shared memories and class cultures.